A molecular dynamics study of intercrystalline crack propagation in nano-nickel bicrystal films with (0 1 0) twist boundary. (December 2016) - Zhang, Yanqiu; Jiang, Shuyong; Zhu, Xiaoming; Zhao, Yanan
Graphical abstract: Highlights: Intercrystalline crack propagation of nano-nickel bicrystal film is investigated. Plasticity of nano-nickel bicrystal film decreases with increasing twist angle. Fracture mode of the nano-nickel bicrystal film is affected by the twist angle. Mechanism of three typical fracture modes was revealed clearly. Abstract: Molecular dynamics simulation was performed to investigate influence of (0 1 0) twist boundary on intercrystalline crack propagation of nano-nickel bicrystal films. The plasticity of nano-nickel bicrystal films decreases with increasing twist angle. Crack arrest in the bicrystal film with twist angle of 0° is attributed to the occurrence of plastic deformation in the whole bicrystal film and hence stress concentration at the crack tip is released. However, new crack initiation in bicrystal films with higher twist angle is attributed to the occurrence of plastic deformation around the grain boundary, where dislocation motion is impeded and thus severe stress concentration is induced.